International Languages And Linguistic Policy (Texas Journal of Multidisciplinary Studies, 2025)
The development of international languages and their influence on global communication have become crucial in the modern world. This paper explores the relationship between international languages and linguistic policies, focusing on the role of language in international diplomacy, trade, and multicultural societies. The study delves into the policies of major world languages, such as English, Spanish, and French, and how these policies shape communication on a global scale. Furthermore, the paper analyzes the linguistic challenges faced by countries adopting international languages and their impact on local languages and cultures. The research highlights the importance of linguistic policy in maintaining linguistic diversity while promoting global communication